Twin births: an overview - Wanjari, Sanjivani Anil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of this study was to investigate the maternal, foetal and obstetric parameters surrounding twin pregnancies. An attempt was made to find out the perinatal mortality and morbidity rates of twin births and to determine the underlying factors responsible for the increase in these rates. Methods: A one year observational study was done at Daga hospital Nagpur, which is a referral maternity hospital receiving a large number of antenatal patients daily. Perinatal mortality and morbidity rates, gestational age at delivery, birth weight, route of delivery, and caesarean section rates were analysed. Results: The commonest presentation in our study vertex/vertex presentation (62%). A large percentage of twins in our study had a normal delivery. 37% women had caesarean section. In our study nearly 17% of the neonates had birth weights <1.5 kg. In 51 % women the first baby had more birth weight than the second twin. Among the 95 twin births (190 twins) studied, we had one discordant twins and one conjoined twins. Conclusions: Twin pregnancies are high risk pregnancies with more obstetrical complications compared to singleton pregnancies. Twin pregnancies have higher perinatal mortality and morbidity rates especially before 34 weeks of gestation. Hence deliveries should be performed in referral centres with competent NICUs.